2020
DOI: 10.1163/22134808-20201487
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Interactions in Virtual Reality: Optic Flow Reduces Vestibular Sensitivity, but Only for Congruent Planes of Motion

Abstract: During exposure to Virtual Reality (VR) a sensory conflict may be present, whereby the visual system signals that the user is moving in a certain direction with a certain acceleration, while the vestibular system signals that the user is stationary. In order to reduce this conflict, the brain may down-weight vestibular signals, which may in turn affect vestibular contributions to self-motion perception. Here we investigated whether vestibular perceptual sensitivity is affected by VR exposure. Participants’ abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 61 publications
3
21
1
Order By: Relevance
“…At the same time, evidence that vection is associated with cybersickness is weak and inconclusive in Palmisano et al's paper (Palmisano et al 2017). Gallagher et al reported significant proof that vection in VR could change vestibular processing and may account for the after-effects (Gallagher et al 2020). Risi and Palmisano identified in their study that participants tend to report a higher level of cybersickness when experiencing stronger vection (Risi and Palmisano 2019).…”
Section: Visual Content Relatedmentioning
confidence: 99%
“…At the same time, evidence that vection is associated with cybersickness is weak and inconclusive in Palmisano et al's paper (Palmisano et al 2017). Gallagher et al reported significant proof that vection in VR could change vestibular processing and may account for the after-effects (Gallagher et al 2020). Risi and Palmisano identified in their study that participants tend to report a higher level of cybersickness when experiencing stronger vection (Risi and Palmisano 2019).…”
Section: Visual Content Relatedmentioning
confidence: 99%
“…Twenty-five healthy right-handed participants volunteered in the study (19 women; mean age= 22.16 years, SD = 7.12 years). The sample size was estimated a priori based on similar experimental procedures (Gallagher et al, 2019;Gallagher et al, 2020), set in advance of testing and was also used as data-collection stopping rule. Participants with a history of neurological, psychiatric, vestibular or auditory disorders were excluded.…”
Section: Participantsmentioning
confidence: 99%
“…For instance, using a rotational chair and timely coupling of physical movement with VR effectively reduced cybersickness symptoms (Ng et al, 2020). Similarly, cybersickness has been shown to improve with Galvanic Vestibular Stimulation (GVS) to artificially mimic vestibular cues in VR (Gallagher et al, 2020;Weech et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The switch of the frame can adjust the height of the seat. This is not a real cabin, but you can already feel very close to the cabin experience [20]. Knowledge acquisition and information acquisition tools based on wireless virtual reality technology will not only improve users' digital abilities and literacy but will also trigger changes in reading forms.…”
Section: Related Workmentioning
confidence: 99%